PERLINDUNGAN HUKUM PEMILIK MEREK TERDAFTAR TERHADAP PRAKTEK USAHA CURANG - Siti Rofikhok; Abraham Ferry Rosando (Gapenas Publisher, 2022)
In commerce, the brand as an intellectual work is important for the smoothness and improvement of trade. A mark has a function as an identifier to distinguish the products of a person or legal entity from those of other people or other legal entities. This is the reason why disputes over trademarks often occur and the need for legal protection for registered trademark owners. Through these legal problems, two formulations of the problem were found, namely how the legal protection of registered trademark owners against fraudulent business practices and what the legal consequences for fraudulent business practices are. This research method uses normative legal research using three approaches, namely: the legal approach, the conceptual approach, and the case approach. The findings of this study are that legal protection for brand owners is only for brand owners who have registered through law number 20 of 2016 concerning trademarks and geographical indications. Mark protection starts from trademark registration, trademark protection for a period of 10 (ten) years and can be extended for the same period of time, taking action against both civil lawsuits, criminal prosecution and administrative steps in the form of rejection of trademark registration and removal of trademarks